Neurovirulence determinants of genetically engineered Theiler viruses. - Fu, J L (1990)
Theiler murine encephalomyelitis viruses (TMEVs) are picornaviruses that cause enteric and neurological disease in mice. The GDVII strain and other members of the GDVII subgroup are highly virulent and cause an acute, fatal polioencephalomyelitis following intracerebral inoculation, whereas the DA stain and other members of the TO subgroup cause a persistent, demyelinating infection. We previously produced a full-length, infectious DA cDNA clone. We now describe the generation of a full-length, infectious GDVII cDNA clone and the subsequent production of intratypic chimeric cDNAs and intratypic recombinant viruses. Inoculation of the recombinant viruses into mice demonstrated that a major determinant of TMEV neurovirulence is within the GDVII 1B (capsid protein VP2)-2C coding region, most likely in the GDVII 1B (VP2)-2A coding region. Genomic sequences 5' to this region of GDVII RNA also contribute to expression of the full neurovirulence phenotype. These data demonstrate the multigenic nature of TMEV neurovirulence, as has been reported for other viruses.